(untitled) (Fiep Bulletin - online, 2013)
This paper aims to present a reflection on the place occupied by football, in postmodernity, in forming the identity of the Brazilian people and as such passion in this everydayness of life of the Brazilian people, may be appropriate for education, especially in field of physical education, aiming at the development of human beings. Sports is entertainment. Football as one of sports entertainment is present in everyday life of the Brazilian people. He’s part of Brazilian culture. We live in a reality of cultural diversity. In this context, discussions about national identity in Brazilian culture have become concerns from several scholars in the field of humanities and social sciences. It is noticeable that the complexity of reality. In the way of being, doing and living of the people are expressed founding elements of identity processes.